Magična moć maski kao paradigma iluzije stvarnosti u drami Ive Vojnovića „Maškarate ispod kuplja” - Pivac, Antonela (Wydawnictwo Naukowe UAM, 2013)
The present paper analyses Ivo Vojnović’s drama Maškarate ispod kuplja by intending to emphasize the importance of carnival masks considered as instruments of liberation of individuals from social conformism. The protagonists of Vojnović’s Maškarate show their non-conformist faces and experience freedom only in carnival season. The carnival is described as the allegory of surreal and phantasmagoric world displaying pseudo-realistic situations that represent the deformed face or, rather, the alter of the masked reality. Masks are, therefore, perceived as shields from the frustrating reality and external influences, whereas life under masks is understood as the perfect model of concealing internal weaknesses and insecurities. The enchanting carnival atmosphere enables the protagonists to openly show the suppressed personality and personal choices. The clear model of searching for the illusion of the truth and the truth of the illusion is also shown, notwithstanding the complicating conditions of the emotional world of the protagonist-symbol who creates false identity provoked and conditioned by external factors. The influence of the Italian grotesque theatre has been reported as well, whereas the similarities have been perceived in particular in the behavioral pattern of the protagonists and perception of time and place as metaphysical categories. The determination of the level of interdependence between the Croatian author and the Italian role models has also been possible. The comparison with the Italian literary contemporaries has been performed by examining the intertextual correspondences in particular related to the selection of the „carnivalesque” motives.
Magical Power of Masks in Ivo Vojnović’s Drama. "Maškarate ispod kuplja" as Paradigm of the Illusion of Reality
Keywords: mask; carnival; persona; alienation; Vojnović; maškarate; grotesque; illusion; deformation